(untitled) (Journal of Intellectual Property Rights (JIPR), 2025)
The birth of Black- box medicine, which relies on complex algorithms and AI to diagnose and treat medical conditions, has sparked significant interest and debate in intellectual property law. As these technologies become integral to modern healthcare, it is important to weigh the upsides and downsides of the technology to protect and regulate them through patents or other IP systems, which is becoming increasingly critical. Algorithms and biological correlations, central to Black- box medicine, face scrutiny under IP protection, especially in patents, due to their potential classification as abstract ideas or laws of nature. The very features that make Black- box medicine innovative and valuable are its reliance on complex algorithms, genetic and biological data, and medical diagnosis and treatment applications. These are the same reasons that render it ineligible for patent protection under the current Indian Patent Regime. Using Black- box medicine also brings significant ethical and social challenges. The lack of transparency in AI systems raises serious concerns about how well we can explain and understand them. This makes it hard to prove they are safe and effective, to interact with them smoothly, and to hold them accountable. Additionally, how different systems work together, how data is shared, and how easily people can access these advanced healthcare solutions must be addressed to avoid widening the Medico-digital divide and to ensure everyone benefits equally from these innovations. Balancing innovation with accessibility, accountability, and fairness will be essential to fully realising the potential of Black- box medicine.